Evaluation of Two Systems for Managing Emergency Poultry Diseases in Intensive Poultry Production Regions - Colby, Michelle M.; Johnson, Yvette J.; Tablante, Nathaniel L.; Hueston, William H. (International Journal of Poultry Science, 2003)
This paper provides an overview of two systems used for the management of infectious disease within the poultry industry on the Delmarva Peninsula. The first system is a paper-based Grid system that was developed in the 1970`s. This system divides the peninsula into a total of 3420 unique locations, each covering approximately 5 square miles. The second system is a Geographic Information System (GIS) database that is currently under construction. Each system is critiqued with respect to several of the criteria established by Klaucke et al. (1998) for the evaluation of a surveillance system: simplicity, flexibility, acceptability, representativeness and timeliness. In addition, the objectives of a disease management system in an intensive poultry production area are discussed. A grid-based system is most appropriately used in situations involving a small, easily managed population or geographic location, especially when funding and geographic resources are limited. When multiple diseases or large geographic areas are the focus of a surveillance and monitoring system, or when several different risk factors are to be examined and funding and adequate resources are available, the use of a GIS-based system provides additional flexibility. The database management component of GIS allows for rapid updating of demographic and disease information, and the linkage of the database component with the spatial coordinates of a GIS provides the ability to examine the effects of several risk factors at the same time.